Emergent neo-customary land tenure and non-indigene smallholders’ access to farmlands in peri-urban Ghana - Ibrahim Abu Abdulai (Discover Sustainability, 2024)
Abstract Land dispossession within the emerging neo-customary land tenure system is not a novel phenomenon in sub-Saharan Africa (SSA). However, the landholding systems across SSA are as diverse as the societies themselves. In Ghana, research on peri-urban land dispossession primarily focuses on centralized areas and indigene landholders, neglecting acephalous and non-indigene smallholders. This gap in knowledge hinders our understanding of how neo-customary land tenure affects land access for non-indigenous smallholder farmers. This paper examines how non-indigene smallholders navigate neo-customary land tenure in peri-urban Wa, Ghana. The study employed a qualitative research design, conducting in-depth interviews and focus group discussions with 56 participants. The findings reveal that large-scale appropriation, covert land sales, and speculation are the primary drivers of land dispossession. The previously unconditional access to land for non-indigene smallholders, based on perpetual usufructuary interest, has also become temporary and conditional on their acceptance of roles as caretaker farmers or sharecroppers. The resulting dispossession and its consequences, such as inadequate subsistence food production, have led to socially undesirable outcomes. The study recommends that the Municipal Assembly and civil society organizations utilize Ghana's Land Act (Act 1036) to advocate for and safeguard the usufructuary interest of non-indigene individuals in land tenure.